Gene-by-environment interactions in COPD - Silverman, Edwin (Henry Stewart Talks, 2007)
Chronic Obstructive Pulmonary Disease (COPD) and cigarette smoking, Gene x environment interactions in COPD, Alpha 1-antitrypsin as a rare major genetic risk for COPD, Familial aggregation of COPD within smokers, Linkage analysis of COPD-related phenotypes, Genetic association studies in COPD
Archived at 2015/09/04